Synthesis of DL-Fluorobenzenamides as Anticonvulsants - Meza-Toledo, Sergio Enrique; Lira-Zárate, Fabiola; Robles-Martínez, Elsa Lizbeth; Peralta-Alvarez, Belen; Cabrera-Cedillo, Fabiola; Peralta-Cruz, Javier; Cruz-Peinado, Claudia; Miñón-López, Humberto (Arzneimittelforschung, 2008)
DL-2-Hydroxy-2-phenyl butyramide (1, CAS 52839-87-9), DL-3-hydroxy-3-phenyl pentanamide (2, CAS 131802-69-2) and DL-4-hydroxy-4-phenyl hexanamide (3, CAS 67880-30-2) are anticonvulsants. Searching for more active compounds, some DL-fluorobenzenamides were prepared and tested: DL-2-hydroxy-2-(3’-tri-fluoromethylphenyl) butyramide (4), DL-2-Hydroxy-2-4’-trifluoromethylphenyl) butyramide (5, CAS 620950-10-9), DL-2-hydroxy-2-[3’][5’-bis(trifluoromethyl)phenyl]butyramide (6, CAS 620950-09-6), DL-3-hydroxy-3-(3’-trifluoromethylphenyl) pentanamide (7), DL-3-hydroxy-3-(4’-trifluoromethylphenyl)pentanamide (8), and DL-3-hydroxy-3-[3’][5’-bis(trifluoromethyl)phenyl]pentanamide (9, CAS 863976-07-2). Compounds 4-9 exhibited anticonvulsant activity in seizures induced by pentylenetetrazol in mice. Incorporation of trifluoromethyl groups in the phenyl ring of 1, 2 and 3 increased their potency. Compounds 4, 6 and 9 exhibited a similar anticonvulsant activity as the reference drug phenobarbital (CAS 50-06-6).
Keywords: Anticonvulsants; Antiepileptics; DL-Fluorobenzenamides, anticonvulsant activity, mice, synthesis